Branding Daya Tarik Wisata terhadap Peningkatan Kunjungan: (Studi Kasus Pantai Camplong Kabupaten Sampang) - Faqih Faqih; Prasetyo Aji Nugroho (Program Studi Ekonomi Syariah Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Tarbiyatut Tholabah, 2025)
Branding is a strategic process of creating and maintaining a positive identity and image of a tourism destination to differentiate it from others and enhance perceived value among visitors. In tourism development, branding is closely related to tourist attractions, including natural uniqueness, cultural diversity, comfort, and memorable travel experiences. Camplong Beach, a coastal tourism destination in Sampang Regency, has significant potential due to its scenic blue sea, natural landscape, and distinctive Madurese culinary offerings. This study aims to examine the tourist attractions of Camplong Beach in increasing visitor numbers and to analyze branding strategies applied to enhance tourist visits. A qualitative descriptive approach was employed using in-depth interviews, field observations, and documentation as data collection techniques. Data were analyzed through data reduction, data presentation, conclusion drawing, and triangulation to ensure validity. The findings indicate that the main attractions of Camplong Beach include natural beauty, local cuisine, supporting facilities, and strategic accessibility. Branding strategies involving visual identity, brand image, brand message, tourist experience, and tourism products have successfully shaped positive perceptions and significantly contributed to increasing tourist interest and visitation.